Personal Hygiene and Environmental Sanitation Integral Hidayatullah Putri Boarding School Depok - Pawitra, Aditya Sukma; Sulistyorini, Lilis; Afriani, Novi Dian; Mukono, J.; Keman, Soedjajadi; Yudhastuti, Ririh; Azizah, R.; Sudarmaji, Sudarmaji; Adriyani, Retno; Prasasti, Corie Indria; Dimjati Lusno, Muhammad Farid; Lestari, Kusuma Scorpia; Diyanah, Khuliyah Candraning; Husnina, Zida; Puji Astuti, Ratna Dwi; Kusuma Wardani, Ratnaningtyas Wahyu; Agustin, Avita Fitri; Kencana, Yulfa Tiara (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Environmental sanitation and personal hygiene are important factors in maintaining student health at school. This community service program was carried out at Hidayatullah Putri Boarding School Depok, West Java, with the aim of improving understanding and practices related to environmental sanitation and clean and healthy living behavior (PHBS). The method used includes three stages: preparation, implementation, and evaluation. In the preparation stage, observation guides, educational materials, and coordination with the school were developed. The implementation stage includes observation of environmental sanitation, FGDs with teachers and school managers, and student education through media such as leaflets, posters, and videos. Evaluation was conducted through pre-test and post-test to measure the effectiveness of education. The results showed an increase in student knowledge, with an average pre-test score of 65.7 and post-test increasing to 84.7, or an increase of 19%. The program also identified several issues such as waste management, bedroom conditions, and limited sanitation facilities. In conclusion, the program was effective in increasing students' awareness of environmental sanitation and personal hygiene and providing practical solutions for sanitation improvement in the school environment.